Structural depiction and analysis of RasGap protein using molecular dynamics simulations - Virupaksha A. Bastikar, Pramodkumar P. Gupta, Piyush Kumar, Alpana Bastikar, Santosh S. Chhajed (Journal of Applied Pharmaceutical Science, 2021)
RasGap is a significantly large protein constituting 1,047 amino acids with vital domains such as SH2, SH3, PH, and C2, N terminal, and RasGap region. However, the structures are available for distinctive domains, and thus in this paper, we predicted the entire 1,047 amino acids’ protein structure using various integrated computational techniques (ab initio, homology modeling, and fragment-based modeling, which were subsequently subjected to molecular dynamics simulation analysis) to predict the structure and analyze the effects of this dynamic feature on the discrete domains. The findings revealed that RasGap protein has dynamic features like polyglycine, polyproline, and polyglutamine regions in the long N-terminal region. All the models exhibited stable conformations with 78.4%–83.1% residues and showed favored regions in the Ramachandran plot and demonstrated a confident c-score of 0.12 and a dope score between −62,050.261719 and −67,629.390625. The N-terminal polyproline region showed a hydrophobicity index ranging from 0.437 to 0.531, while the SH2_1 ranged from 0.633 to 0.68, SH3_2 ranged from 0.626 to 0.71, and SH3 ranged from 0.589 to 0.651. The molecular dynamics simulations also revealed the opening of the cavity region. Polyproline, with SH2_1, SH3, and SH2_2 domains, is a known and responsible factor in the formation of RasGap– Nck1 complex. Hence, opening a cavity in the studied region of RasGap protein correlates a strong relationship in the formation of the cavity region, which can be further studied in its interaction with the Nck1 protein.
Keywords: RasGap, molecular modeling, simulation, homology modeling.